Longitudinal impact of oral health on geriatric syndromes and clinical outcomes in community-dwelling older adults - Jihye Lim; Hyungchul Park; Heayon Lee; Eunju Lee; Danbi Lee; Hee-Won Jung; Il-Young Jang (BMC Geriatrics, 2021)
Abstract Background Oral health is essential for daily living and plays a pivotal role in overall health conditions and well-being. This study evaluated the impact of self-reported oral health on geriatric conditions, institutionalization, and mortality. Methods This study analyzed the population of the Aging Study of Pyeongchang Rural Area that had undergone geriatric assessments between 2016 and 2017. The oral health status of the participants was determined using three items from the General Oral Health Assessment Index, and the participants were classified into three groups according to the total sum of the scores as good (3), fair (4–7), or poor (8–15). The outcomes were the incidence of geriatric syndromes at 2 years and the composite outcome of mortality and institutionalization. Results Among the 1189 participants, 44.1 % were women, and the mean age of the study population was 75.0 years. Good, fair, and poor oral health were observed in 597 (50.2 %), 406 (34.1 %), and 186 (15.6 %) individuals, respectively. Worsening oral health status was associated with the incidences of various geriatric syndromes at follow-up, and these associations were attenuated after adjusting for baseline demographic and geriatric parameters. Similarly, the significant association between baseline oral health status and the incidence of the composite outcome was attenuated after adjusting for demographic and geriatric parameters. Conclusions Oral health affected the geriatric health conditions in this prospective, longitudinal cohort of community-dwelling older adults. The correlations and interactions of oral health status with other functional parameters may deserve consideration as a geriatric domain.